METRICS OF MANAGEMENT AND CONTROL REQUIREMENTS PROCESSES IN PROJECTS - Husieva, Yu. Yu.; Martynenko, O. S.; Kadykova, I. M.; Chumachenko, I. V. (Radio Electronics, Computer Science, Control, 2018)
Context. The processes of requirements management are a key factor in the success or failure of the project. Researches in the field of project management indicate that these processes are not formalized. Thus, there is need to develop and formalize methods of requirements management and control, particularly for projects which are carried out by combined or traditional methodologies. Objective of the article is formalizing of requirements management processes metrics in projects. The object of the research is management and control requirements processes of projects, the subject of the study – metrics that characterize the requirements of the project. Method. Methods used are analysis and synthesis, methods of fuzzy sets and operations on matrices. The use of a model that establishes relationships between individual characteristics of the project (risks, resources, requirements, stakeholders and decision-makers of the project) through WBS is proposed. A formalization of model metrics is proposed that will keep track of the project and identify project stakeholders through the defined areas. Results. Based on the comparison of WBS with a hierarchical structure of requirements, risks, resources and organizational structure of the project method of formalizing metrics requirements management project is developed. The proposed method allow to track the performance of project stakeholders’ requirements according to the actual amount of resources spent by analogy with the method of earned value. Adaptability to the traditional project management processes lets you use the original data – assets of the project and standard software (eg, MS Project, OpenProj) for the practical implementation of the method. Conclusions. The proposed method formalizes requirement management processes in the project, determines resource and risk load of requirements, supplementing the existing requirements classification models with these metrics. The proposed method can also provide metrics for evaluation the performance of the project team and project stakeholders classification. The conducted experiments have confirmed the efficiency of the proposed mathematical software and allow recommending it for use in practice for making project decisions about change management and requirements management of the project. Prospects for further research may include developing of software that will implement the proposed method.